A Comparison of Intracranial Volume Growth in Normal Children and Patients With Metopic Craniosynostosis. Issue 1 (January 2020) - Cronin, Brendan J.; Brandel, Michael G.; McKee, Ryan M.; Hashmi, Asra; Oviedo, Parisa; Buckstaff, Taylor; Cahill, Gabrielle; Mannix, Emily; Reid, Chris M.; Lance, Samuel; Vinocur, Daniel; Meltzer, Hal S.; et al.
Abstract : Background: The impact of metopic craniosynostosis on intracranial volume (ICV) and ICV growth is unclear. In addition, the relationship between head circumference (HC) and ICV in these patients is not previously described. Methods: A retrospective review of 72 patients with metopic craniosynostosis was performed. The ICVs were calculated from manually segmented preoperative computed tomography scans. Magnetic resonance imaging data for 270 healthy children were available. The ICVs were calculated in FreeSurfer. First, a growth curve for metopic patients was generated and a logarithmic best-fit curve was calculated. Second, the impact of metopic craniosynostosis on ICV relative to healthy controls was assessed using multivariate linear regression. Third, the growth curves for metopic patients and healthy children were compared. Pearson's correlation was used to measure the association between HC and ICV. Results: Mean metopic ICV was significantly lower than normal ICV within the first 3 to 6 months (674.9 versus 813.2 cm 3 ; P = 0.002), 6 to 9 months (646.6 versus 903.9 cm 3 ; P = 0.005), and 9 to 12 months of life (848.0 versus 956.6 cm 3 ; P = 0.038). There was no difference in ICV after 12 months of age ( P = 0.916). The ICV growth in patients with metopic craniosynostosis is defined by a significantly different growth curve than in normal children ( P = 0.005). The ICV and HC were highly correlated across a broad range of ICVs and patient age ( r = 0.98, P < 0.001). Conclusion: Patients with metopic craniosynostosis have significantly reduced ICVs compared to healthy children, yet greater than normal ICV growth, which allows them to achieve normal volumes by 1 year of age. The HC is a reliable metric for ICV in these patients. Abstract : Supplemental Digital Content is available in the text